PERSEPSI WISATAWAN TENTANG DESTINASI WISATA PANTAI PASIR JAMBAK KOTA PADANG - Pakpahan, Rio Naldo; Silfeni, Silfeni; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The purpose of research is to determine the tourist perceptions about the tourdestination of PantaiPasirJambak Padang City. This research consists of fiveindicators are: tour attraction, pre tool, tool, infrastructure and society, . This type ofresearch is descriptive research using survey method. Population in this researchamounted to 728 tourist. Sampling technique is non probability sampling, usinginsidental sampling. Sample number in this research amounted to 89 tourist. Datacollection using a questionnaire based on a Likert scale that tested for validity andreliability. Based on the results of the study concluded that in general the touristperceptions about the tour destinationofPantaiPasirJambak Padang City good enoughin mean 142,03 between range 126 -< 154.